Challenges in Ungoverned Spaces and the Crisis of Insecurity Across the Sahel - Imam, Mukhtar; Tijjani, Chubado Babbi (Advances in Social Sciences Research Journal, 2024)
The paper tries to underscore the challenges associated with ungoverned spaces and the crisis of insecurity in the Sahel. It tries to look into the dominant narratives and perspectives on the immediate and remote causes of the crisis and how it has destabilized the region. It also looks at the various conterminous and contentions interpretation of the terms, ‘space’, and ‘ungoverned’ in a bid to ascertain the range, scope and borders of governance. The paper relied on existing materials as sources of data. It finds amongst other things that some domestic and external triggers have given rise to the prolonged and contracted crisis in the region, some of which include; political representation, marginalization, unequal allocation of resources and the gap in wealth distribution. It highlights the impact of the proliferation and spread of light and small weapons in the region and how this has further intensified and balkanized the crisis and instability. It concludes by demystifying claims that the conflict seeks to serve the interest of spreading the so-called concept of ‘Islamic Jihad’.